Global prevalence of occupational injuries among sanitation workers: a systematic review and meta-analysis - Tolera, Sina Temesgen; Gobena, Tesfaye; Assefa, Nega; Geremew, Abraham (Frontiers in Public Health, 2024)
Background: In the sanitation industry, occupational injuries among sanitary workers (SWs) are common due to unsafe working conditions and poor working surroundings. Even yet, there hasn't been much focus on it thus far, and no comprehensive meta-analysis on occupational injuries among sanitary workers globally has been conducted.: To conduct systematic review and meta-analysis on occupational injuries among sanitary workers in worldwide from 2000 -2023 Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was used for screening diagram. Published articles searched by different engines between 2000 and 2023. The keywords (Occupation Job Injuries *OR Work Injuries *OR Occupational Injuries AND Sanitary workers (Street sweepers [SS] *OR health facilities cleaners [HCFC]) *OR Solid waste collectors [SWCs] *OR Sewage workers [STW] were used. Stata Version 17MP was used for data analysis. The random-effect model and Restricted Maximum Likelihood approaches were used to compute the generic effect size (Random-Effect REML Model) at confidence interval of 95%(CI:95%) where a p-value less than 0.05 was statistically significant. The studies were searched through PubMed (n=34), Medline (n=39), Embase (n=23), Global Health (n=37), other (n=54), and from review studies (n=10). Thus, from a total of 197 studies, only 23 were fully met inclusion criteria. Out 8138 SWs, 4469(55%), 2317(28%), 1144 (14%) and 208 (3%) were shared by SWCs, SS, HCFC, and SS with SWCs, respectively. Globally, the pooled prevalence of occupational injuries among SWs was 36.49% (95%CI: 0.29-0.45). Of this, 39.14 % (95%CI: 0.24 -0.53) and 35.22% (95%CI: 0.36-0.44) were obtained from high income low-income countries, respectively. Year-by-years analysis, it was 36.70% (95%CI:0.28-0.46 from 2001 to 2015 and 36.45% (95%CI:0.25-0.48 from 2016 to 2022). The overall heterogeneity of the studies was 90.03% for I-squared of 214.43 at p-value < 0.05, indicating it is statistically significant heterogeneity among the eligible studies. Sanitation and hygiene workers are at increased risk for occupational-related conditions. This is as the result of little attention for occupational safety and health services in the work setup. Therefore, the review advised that necessitates policy amendment, national proclamations as well as international initiative of occupational health and safety services in order to alleviate these risks.